2011
DOI: 10.2298/jsc100406014j
|View full text |Cite
|
Sign up to set email alerts
|

A selective laser melted Co-Cr alloy used for the rapid manufacture of removable partial denture frameworks: Initial screening of biocompatibility

Abstract: The aim of this study was to determine the cytotoxicity of a Co-Cr alloy used for the rapid manufacture of removable partial denture frameworks using murine fibroblasts L929 cell lines and three test methods: the MTT assay, the agar diffusion test (ADT) and the dye exclusion test (DET). Two groups of disc specimens (5 mm diameter, 1 mm thick) were fabricated. The first group was cast using a conventional method (CM) in a Nautilus CC casting. The second group was fabricated using selective las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Then, the alloy framework was processed using the cast mold method Kanazawa et al [7] Milling Kanazawa et al used CBCT scans of prostheses and denture teeth and digitally arranged the teeth. The prosthesis base was fabricated from a block of acrylic resin using CNC milling, following which the teeth were manually bonded in the holes created in the denture base Jevremović et al [24] Rapid prototyping Jevremović et al studied about alloys used for fabricating prostheses using SLM. They concluded that Co-Cr alloys did not have cytotoxic effects, while some metals commonly resulted in side effects, mentioning that 30 alloys showed similar characteristics used in SLM for cast alloy processing Goodacre et al [9] Milling Goodacre et al scanned silicone impressions by neutral zone technique for scanning, additionally recorded interocclusal relations, then teeth were arranged digitally.…”
Section: Techniques and Materials Used F O R D E N T A L C O M P U T mentioning
confidence: 99%
“…Then, the alloy framework was processed using the cast mold method Kanazawa et al [7] Milling Kanazawa et al used CBCT scans of prostheses and denture teeth and digitally arranged the teeth. The prosthesis base was fabricated from a block of acrylic resin using CNC milling, following which the teeth were manually bonded in the holes created in the denture base Jevremović et al [24] Rapid prototyping Jevremović et al studied about alloys used for fabricating prostheses using SLM. They concluded that Co-Cr alloys did not have cytotoxic effects, while some metals commonly resulted in side effects, mentioning that 30 alloys showed similar characteristics used in SLM for cast alloy processing Goodacre et al [9] Milling Goodacre et al scanned silicone impressions by neutral zone technique for scanning, additionally recorded interocclusal relations, then teeth were arranged digitally.…”
Section: Techniques and Materials Used F O R D E N T A L C O M P U T mentioning
confidence: 99%
“…18 AM could also be very useful in orthodontics because of the complex shape of teeth and the customized production of appliances. [2][3][4][5][6][7][8][9][10] The FSG appliance is completely individually designed for patients with a Class II relationship due to a retrognathic mandible. The FSG appliance, in closing the jaw, guides the mandible anteriorly and inferiorly to correct the sagittal and vertical deficiency, which achieved an increase in the mandibular length and the forward and downward movement of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its suitability for the low-volume production of complex parts, AM technology very soon found its way into medical and especially dental applications. [1][2][3][4][5][6][7][8][9] Until recently, orthodontic applications have been lagging behind, but with the newest research and applicable solutions 10 it is becoming clear that AM technologies will also have to be considered in this field.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Jevremovic et al tested the biological properties of this Co–Cr alloy and found that it had good biocompatibility, with no permanent damage to the cell function and, therefore, it was rated as a noncytotoxic alloy. In a previous study they noted that some Co–Cr alloys available for SLM can contain nickel, a metal commonly associated with side effects, but once more they concluded that that alloy did not have a cytotoxic potential. According to them, this alloy used for SLM has the same characteristics of those used in the cast alloy technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a previous study they noted that some Co–Cr alloys available for SLM can contain nickel, a metal commonly associated with side effects, but once more they concluded that that alloy did not have a cytotoxic potential. According to them, this alloy used for SLM has the same characteristics of those used in the cast alloy technique. They also cited the importance of the manual finishing procedure of the metal to improve the already good condition of the surface result of the SLS procedure—homogeneous, with few pores and a fine microstructure .…”
Section: Literature Reviewmentioning
confidence: 99%